Comparative analysis of approches in developing Android applications using Xamarin technology - Bartkiewicz, Michał; Dziedzic, Adrian (Journal of Computer Sciences Institute, 2018)
Article shows analysis of Xamarin technology in two modes: Xamarin Forms and Xamarin Native, used for developing applications for mobile devices with Android system. Comparison concerns the number of generated lines of code, performance of each part and size of installed application and size of apk installation file. Analysis was based on two identical applications created using both approaches. As a result of the analysis the more efficient approach for given purpose has been indicated.